1998
DOI: 10.1046/j.1365-2044.1998.00369.x
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of ginger root in the prevention of postoperative nausea and vomiting after outpatient gynaecological laparoscopy

Abstract: SummaryWe have evaluated the effects of the volume and speed of administration of local anaesthetic during peribulbar anaesthesia. One hundred and forty patients scheduled for cataract surgery were randomly allocated to one of four groups of 35. Each patient received an injection of the same mixture of lignocaine, bupivacaine and hyaluronidase. Patients in group A were given 9 ml at a speed of 5 ml.min À1 , group B were given the same volume at 12 ml.min À1 , group C were given 13.5 ml at 5 ml.min À1 and group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 19 publications
(19 reference statements)
1
55
0
5
Order By: Relevance
“…nih.gov), EMBASE (http://stneasy.fiz-karlsruhe.de) und dem Cochrane controlled trials register (http://www.cochrane.de) durchgeführt. Anhand der Begriffe «ginger OR ingwer», «ginger AND nausea», «ginger AND vomiting» wurde systematisch nach randomisierten klinischen Studien zum Thema [8,[10][11][12][13], in einer weiteren Studie Laparotomien und vaginale Hysterektomien untersucht [9]. In zwei dieser Untersuchungen [9,11] [10].…”
Section: Materials Und Methodenunclassified
See 1 more Smart Citation
“…nih.gov), EMBASE (http://stneasy.fiz-karlsruhe.de) und dem Cochrane controlled trials register (http://www.cochrane.de) durchgeführt. Anhand der Begriffe «ginger OR ingwer», «ginger AND nausea», «ginger AND vomiting» wurde systematisch nach randomisierten klinischen Studien zum Thema [8,[10][11][12][13], in einer weiteren Studie Laparotomien und vaginale Hysterektomien untersucht [9]. In zwei dieser Untersuchungen [9,11] [10].…”
Section: Materials Und Methodenunclassified
“…Die Kommission E des damaligen Bundesgesundheitsamtes publizierte daraufhin eine Positivmonographie für die Indikationsgebiete «Dyspeptische Beschwerden» sowie «Verhinderung der Symptome der Reisekrankheit» [7]. Klinische Studien wurden darüber hinaus auch zum Thema Übelkeit und Erbrechen in der postoperativen Phase (PONV = postoperative nausea and vomiting) [8][9][10][11][12][13] sowie zum Thema Schwangerschaftsübelkeit bzw. Hyperemesis gravidarum durchgeführt [14][15][16][17].…”
Section: Introductionunclassified
“…18,19 The powdered rhizome of Z officinale has long been used as a herbal remedy for gastrointestinal disorders such as nausea, vomiting, dyspepsia, constipation, flatulence, and colic. 18,19 Modern scientific research has also confirmed that ginger might be effective against nausea and vomiting induced by motion sickness, sea sickness, surgery, and pregnancy. [20][21][22][23][24][25] With respect to CINV, there is evidence on the efficacy of ginger in animals.…”
Section: Introductionmentioning
confidence: 99%
“…Drei Studien zeigten ein negatives Ergebnis [11,13,21], drei weitere ein positives [9,10,14]! Morin et al [22] poolten die Daten dieser sechs Studien und kamen zu dem Ergebnis, dass für Ingwer zur Behandlung von postoperativer Nausea keine Signifikanz vorhanden ist.…”
Section: Klinische Studien 2000-2009unclassified